PENGARUH KUALITAS PELAYANAN, PROMOSI DAN KETEPATAN WAKTU PENGIRIMAN TERHADAP KEPUASAN PELANGGAN PADA PENGGUNA APLIKASI ALFAGIFT DI BANDAR LAMPUNG - Dwi Ayu Sularsih; Driya Wiryawan (Yayasan Nusantara Hasana Berdikari, 2025)
Advances in digitalization technology make it easier to carry out daily activities, especially shopping activities online is a trend that continues to grow in the digital era, including among the people of Bandar Lampung. Alfagift application, as one platform shopping online, offers easy shopping with various attractive features. However, as usage increases, issues arise such as inconsistent service quality, questionable effectiveness of promotions, and on time delivery that does not match what is offered and sometimes does not meet customer expectations. The problem of this research is whether service quality, promotions and on time delivery have an effect on customer satisfaction for Alfagift application users. The aim of this research is to determine the influence of service quality, promotions and timeliness of delivery on customer satisfaction among Alfagift application users in Bandar Lampung. The method used in this research is a quantitative approach with data collection through surveys and questionnaires as research instruments and a sample of 100 people using the method purposive sampling. The data analysis method used in this research is multiple linear regression technique. The calculation results from the determination test (R2) shows that 82% of customer satisfaction is influenced by the independent variables of service quality, promotions and on time delivery. Meanwhile, the remaining 18% is influenced by other variables not studied. So it can be concluded that service quality, promotions and on time delivery can influence customer satisfaction.